Enamel defects and ectopic eruption in a child with Usher syndrome and a cochlear implant - RICHARD BALMER & STEPHEN A. F. FAYLE (IAPD and Blackwell, 2007)
Usher syndrome is a genetic disorder consisting of progressive loss of vision and hearing.